The bear went over the mountain - Kotzwinkle, William (New York : Doubleday, 1996)
A bear takes America by storm when he finds a book manuscript in the woods, and after reading it, decides to head for New York to seek fame and fortune in the literary world.
Booklist starred.
School Library Journal.
Wilson's Fiction.
Adult
Keywords: Authors and publishers -- United States -- Fiction; Bears -- United States -- Fiction; American satire; Authors and publishers -- Fiction; Bears -- Fiction; Fantastic fiction; Humorous stories; Satire